Pattern of skin diseases in patients attended OPD of Dermatology and Venereology in a tertiary care teaching hospital in Bangladesh - Yousuf, Abul Kalam Mohammad; Joarder, Yasmin; Aktar, Ayasha; Hoq, Md. Nazmul; Rahman, Mushfika; Akter, Farhana; Begum, Halima; Akhtar, Md. Rafiqul; Rahman, AKM Shahidur (Bangladesh Journal of Physiology and Pharmacology, 2014)
Background: Skin problems are one of the most common health problems seen in the developing countries. Objective: To assess the pattern of skin diseases most commonly encountered in Dermatology & Venereology Outdoor Patient Department (OPD) of Northern International Medical college Hospital (NIMCH). Materials and Methods: This cross sectional study was carried out in the Dermatology & Venereology OPD of NIMCH, Dhanmondi, Dhaka, Bangladesh, during the period of January 2012 to December 2012. A total of 1169 patients (511male and 658 female) aged 10-44 years, attended in the OPD in which 969 patients (450 male and 519 female) were found to have dermatological problems. Data were analyzed by using SPSS soft-ware version 18. Results: The pattern of skin diseases was higher in females (53.6%) than in males (46.4%). The most common disorders seen in outpatient department is eczema (23.7%) followed by fungal infection (15.5%), scabies (13.4%) and acne vulgaris (11.9%). A remarkable part (41.4%) of the patients was illiterate. Majority of the patients (67.6%) belonged to poor socio-economic class. 61.4 % patients were residing in overcrowded homes and 53% patients were not maintained personal hygienic standards Conclusion: This study gives a fair picture of pattern of common skin diseases in urban Dhanmondi and its surrounding locality, Dhaka. From this study, it can be concluded that better health education, maintaining personal hygiene, improvement in the standard of living, proper case diagnosis and proper treatment may remain of importance in managing common skin diseases. http://dx.doi.org/10.3329/bjpp.v29i1-2.20061 Bangladesh J Physiol Pharmacol 2013; 29(1&2) : 8-11